2020
DOI: 10.1177/0363546520917386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patient Characteristics in the Success of Nonoperative Treatment of Anterior Cruciate Ligament Injuries

Abstract: Background: Anterior cruciate ligament (ACL) tears can either be treated nonoperatively with physical therapy and then treated operatively if persistent instability is present, or be directly treated operatively. Advantages of early ACL reconstruction surgery include shorter time from injury to surgery and potentially fewer meniscal injuries, but performing early ACL reconstruction in all patients results in surgery in patients who might not need ACL reconstruction. It is important to assess in which patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…A recent study showed that approximately 60% of patients require ACL reconstruction after nonoperative treatment, but rates increase to 90% for those aged <25 years and 83% for those participating in Tegner level ≄7 sports. 54 As such, it is important to be aware that early surgery is likely to be cost-effective when the likelihood to require surgery is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that approximately 60% of patients require ACL reconstruction after nonoperative treatment, but rates increase to 90% for those aged <25 years and 83% for those participating in Tegner level ≄7 sports. 54 As such, it is important to be aware that early surgery is likely to be cost-effective when the likelihood to require surgery is high.…”
Section: Discussionmentioning
confidence: 99%
“…The American Journal of Sports Medicine 2023;51(4):1106-1116 DOI: 10.1177/03635465211069356 Ó 2022 The Author(s) delaying these procedures is that this increases the time from injury to surgery, may lead to quadriceps atrophy, 52 and potentially increases the risk of meniscal and chondral damage. 11,54 Therefore, it might be advantageous to indicate patients early for surgery to enable a faster return to work or sports activities. Furthermore, recent studies with modern surgical techniques and rehabilitation protocols did not associate early surgery with higher risk for postoperative stiffness (Table 1).…”
mentioning
confidence: 99%
“…FĂŒr die konservative Therapie stehen im hochambitionierten Bereich neben einzelnen Fallbeispielen/Studien kaum Daten zur VerfĂŒgung [80][81][82]. DarĂŒber hinaus wird die Analyse dadurch erschwert, dass in vielen Untersuchungen konservativ versorgten Kreuzbandpatienten grundsĂ€tzlich eine Reduktion des sportlichen Anspruchs empfohlen wird [81,83]. Erstaunlicherweise sind die Unterschiede im Vergleich zu einer gematchten operativ versorgten Gruppe trotz dieser Empfehlung nicht signifikant [80,81].…”
Section: Entwicklung Einer Kniegelenkarthrose Nach Einer Rekonstrukti...unclassified
“…Recently, patients have reported low pain scores, minimal awareness of their injured knee, and short recovery times 7,20-24 . For severe knee dislocations, arthroscopic ligament repair may be performed in a single-stage fashion for certain tear types 13,25-28 , thus avoiding the issues involved in a staged reconstruction 29-33 .…”
mentioning
confidence: 99%